VISUALIZATION OF WAVE-INDUCED SUSPENSION PATTERNS OVER TWO-DIMENSIONAL BEDFORMS - Villard P.V.; Osborne Ph.D. (My University, 2002)
High spatial and temporal resolution measurements of suspended sand concentration (c ) over vortex ripples were collected with a three-transducer acoustic backscatter sensor (ABS) array, under irregular `natural' waves in a multidirectional wave basin. These measurements permit two-dimensional visualization of the movement of sediment-laden vortices over an individual vortex ripple under a series of waves. Patterns of sediment motion were tracked through consecutive zero-crossings in the horizontal velocity (U ) record measured at 0·05 m above the ripple crest elevation. It was possible to trace the advection of individual sediment-laden vortices at the zero-crossings. During 73% of these events, shedding and advection of coherent suspension events occurred before the flow reversal associated with the zero-crossing. This may be caused by the bedforms retarding the near-bed flow inducing the eddy shedding before the zero-crossing. While at maxima in U, secondary suspension events with low c were observed to pass over the ripple crest moving with U measured at 0·05 m. This pattern is attributed to vortex shedding from adjacent bedforms and/or antecedent suspension events. The most energetic events appeared to persist for several wave cycles and reached heights of ≈0·20 m. These suspension events appeared to be more persistent when smaller waves follow larger waves, possibly as a result of weaker reversals in vorticity. Although the events appeared to be vertically coherent in the time series from the individual transducers, it is apparent through visualization that these events are associated with the pairing of antecedent and developing vortices.
Keywords: ACOUSTIC BACKSCATTER SENSOR; FLUME; RIPPLES; SAND TRANSPORT; VORTICES